A high-toughness phenolic adhesive and preparation method thereof
A phenolic adhesive is enhanced with modified calcium carbonate and a hyperbranched modifier to form a core-shell structure, addressing toughness issues and improving mechanical strength for diverse industrial uses.
Patent Information
- Application Number
- CN202410376600.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-29
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-03-29
AI Technical Summary
Phenolic resin adhesives exhibit poor toughness due to their rigid polymer network structure, which limits their application in industries requiring flexibility and impact resistance, and existing modification methods either affect compatibility or dispersibility, leading to performance degradation.
A high-toughness phenolic adhesive is prepared by compounding phenolic resin with modified calcium carbonate, which is treated with a hyperbranched modifier to form a core-shell structure, enhancing toughness through a graft copolymerization process.
The modified phenolic adhesive demonstrates improved toughness and mechanical strength, with enhanced crack resistance and energy absorption, making it suitable for demanding applications.
Smart Images

Figure BDA0004767232920000031 
Figure BDA0004767232920000041 
Figure BDA0004767232920000151
Abstract
Description
Technical Field
[0001] The invention belongs to the field of adhesives, and in particular relates to a high-toughness phenolic adhesive and a preparation method thereof. Background Art
[0002] Phenolic resin adhesive is made of phenolic resin. Phenolic resin has a large polarity and has good adhesion to metals and most non-metals. It is widely used due to its high bonding strength, water resistance, heat resistance, wear resistance and good chemical stability. Modified phenolic resin adhesive can be used as structural adhesive to manufacture honeycomb structures, brake pads, grinding wheels, emery paper and composite materials, etc. It has been widely used in aerospace, machinery, military industry, etc.
[0003] However, phenolic resin has poor toughness. From its structural point of view, the main reason is that the condensation product of phenolic resin contains a large number of phenolic hydroxyl groups and methylene groups, lacks flexible functional groups, and the aromatic nuclei are only connected by methylene groups in the cured polymer network structure. The internal resistance in the polymer network structure is large, which hinders the internal rotation of the aromatic ring and further makes the phenolic resin more brittle.
[0004] At present, there are the following methods in the prior art to modify phenolic resins, one is to add external toughening agents such as natural rubber, nitrile rubber, silicone and thermoplastic resins, etc.; the second is to add internal toughening agents such as etherifying phenolic hydroxyl groups, introducing long alkyl chains and other flexible groups between phenol cores, or using inorganic reinforcing fillers to change brittleness, but there are also defects, such as adding external toughening agents is physical blending, there will be different degrees of grafting or block copolymerization during the curing process, the content is high, and it will also affect the compatibilizer with the phenolic resin matrix, the use of internal toughening agents such as cashew nut oil, the viscosity of the phenolic resin system will increase rapidly, the fluidity will deteriorate, and its processing performance will be affected, and the addition of reinforcing fillers, there is also a phenomenon of easy agglomeration, it cannot be more evenly dispersed in the phenolic resin matrix, affecting its reinforcing effect. Further limit the wide application of phenolic resin adhesives in the industry, therefore need to develop a method that can not only not affect the performance of phenolic resin but also improve the toughness of phenolic resin. Summary of the invention
[0005] In order to solve the technical problems mentioned in the background technology, the object of the present invention is to provide a high-toughness phenolic adhesive and a preparation method thereof.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A high-toughness phenolic adhesive, comprising the following materials in parts by weight:
[0008] 100 parts of phenolic resin, 15-20 parts of modified calcium carbonate, 5-8 parts of curing agent, 5-8 parts of diluent, 3-5 parts of defoaming agent and 2-3 parts of antioxidant;
[0009] Modified calcium carbonate is prepared by the following method:
[0010] Step A1: Mix calcium carbonate and deionized water and add them to a reactor, control the stirring rate to 1500-2000 r / min, and stir for 20 minutes to obtain a calcium carbonate suspension; then add sodium hydroxide and stearic acid to the reactor, heat to 70-75° C., and stir for 1 hour to obtain modified calcium carbonate;
[0011] Furthermore, the solid content of the calcium carbonate suspension is 20%; the dosage ratio of calcium carbonate, sodium hydroxide and stearic acid is 10g:0.06g:0.15-0.2g;
[0012] Step A2: Place the modified calcium carbonate and anhydrous ethanol in an ultrasonic disperser, ultrasonically disperse for 30 minutes, transfer to a reactor, add a hyperbranched modifier, control the stirring reaction rate to 200-300 r / min, heat to 55-65° C., stir and react for 5-6 hours, filter and wash the filter cake 2-3 times, then transfer to an oven, control the oven temperature to 100° C., and vacuum dry for 24 hours to obtain modified calcium carbonate;
[0013] Further, the usage ratio of modified calcium carbonate, anhydrous ethanol and hyperbranched modifier is 5-10 g: 50 g: 100 mL;
[0014] The silane coupling agent structure in the hyperbranched modifier reacts with the hydroxyl group on the surface of the modified calcium carbonate and adsorbs it into the cavity of the hyperbranched modifier to form a core-shell structure.
[0015] The hyperbranched modifier is prepared by the following method:
[0016] Step B1: dipentaerythritol, γ-glycidyloxypropyltrimethoxysilane, triethylamine and DMF were mixed and added into a reaction kettle, the reaction rate was controlled to be 150-200 r / min, the temperature was raised to 60-70° C., and benzene was added after stirring for 2-3 hours, and the intermediate 1 was obtained by rotary evaporation under reduced pressure;
[0017] Furthermore, the usage ratio of dipentaerythritol, γ-glycidyloxypropyltrimethoxysilane, triethylamine and DMF is 0.05 mol:0.3 mol:1.5-2 mL:100 mL; the usage ratio of DMF and benzene is 1 mL:3 mL;
[0018] Dipentaerythritol and γ-glycidyloxypropyltrimethoxysilane undergo a ring-opening reaction to graft the silane coupling agent onto the dipentaerythritol molecule. The structure of intermediate 1 is shown below:
[0019]
[0020] Step B2: diethanolamine and anhydrous methanol were mixed and added to a reactor, the stirring reaction rate was controlled to be 300-400 r / min, and the mixture was stirred in a nitrogen atmosphere until it was completely dissolved, and then methyl acrylate and potassium carbonate were added, the temperature was raised to 35-40° C., and the mixture was stirred for 4-5 hours, and then vacuum rotary evaporation was performed to obtain intermediate 2;
[0021] Furthermore, the usage ratio of diethanolamine, methyl acrylate, potassium carbonate and anhydrous ethanol is 0.5 mol: 0.8 mol: 1.5-1.8 g: 200 mL;
[0022] Diethanolamine is completely dissolved in anhydrous methanol, and then, under the catalytic action of potassium carbonate, the secondary amine and the carbon-carbon double bond in methyl acrylate undergo an addition reaction, grafting methyl acrylate onto the diethanolamine molecule. The structure of intermediate 2 is shown below:
[0023]
[0024] Step B3: taking intermediate 1, p-toluenesulfonic acid and NMP and mixing them into a reactor, controlling the stirring reaction rate to 200-300r / min, heating to 90-100°C and stirring continuously until intermediate 1 is completely dissolved, then adding intermediate 2, and then heating to 130°C, stirring and reacting for 2h, adding chloroform, extracting, and drying to obtain a hyperbranched modifier;
[0025] Furthermore, the usage ratio of intermediate 1, intermediate 2, p-toluenesulfonic acid and NMP is 0.01 mol: 0.06 mol: 0.3-0.5 g: 50 mL; the usage ratio of NMP and chloroform is 1 mL: 2 mL;
[0026] Intermediate 1 and intermediate 2 continue to react to form a hyperbranched polymer with terminal hydroxyl groups.
[0027] The high toughness phenolic adhesive is prepared by the following method:
[0028] Phenolic resin, modified calcium carbonate, curing agent, defoaming agent, diluent and antioxidant are mixed and added into a reactor, the stirring reaction rate is controlled to be 1000-1500r / min, the temperature is raised to 70-80°C, stirred for reaction for 1-2h, and then cooled to room temperature to obtain a high-toughness phenolic adhesive.
[0029] Beneficial effects of the present invention:
[0030] The invention discloses a high-toughness phenolic adhesive. The high-toughness phenolic adhesive uses a phenolic resin as a matrix, and is modified by compounding a hyperbranched modifier to modify calcium carbonate. The hyperbranched modifier is a three-dimensional network structure, and contains a large number of cavities inside its molecules. The calcium carbonate molecules can be coupled through the silane coupling agent structure on its molecular chain, and the calcium carbonate molecules are adsorbed in the cavities of the hyperbranched modifier to form a core-shell structure, which can not only improve the agglomeration phenomenon of calcium carbonate in the phenolic resin matrix, but also improve the brittleness of the phenolic resin matrix, thereby achieving the effect of toughening and strengthening. The hyperbranched modifier contains a large number of terminal hydroxyl groups on the shell structure molecule, which can react with the hydroxyl groups in the phenolic resin matrix. The structural combination forms a graft copolymer. On the one hand, it can effectively improve the phenomenon that the phenolic hydroxyl group and the methylene group in the molecular chain of the phenolic resin matrix are easily oxidized, and the mechanical strength of the phenolic resin matrix is improved. On the other hand, the expanded dendritic structure in the hyperbranched modifier provides more free volume for the phenolic resin matrix, which can be dispersed and transmitted when the phenolic resin is impacted, thereby improving the toughness of the phenolic resin matrix. Moreover, as the calcium carbonate molecules of the core structure, when the stress continues to be transmitted and dispersed to the calcium carbonate molecules through the cavity, the small calcium carbonate molecules will produce more cracks and plastic deformation areas, and absorb energy again, further strengthening the toughness and mechanical strength of the phenolic resin matrix. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] The specific implementation process of preparing a high-toughness phenolic adhesive in this embodiment is as follows:
[0034] 1) Preparation of modified calcium carbonate:
[0035] a1: 10g of calcium carbonate and deionized water were mixed and added to a reactor, the stirring rate was controlled to be 1500r / min, and after stirring for 20min, a calcium carbonate suspension with a solid content of 20% was obtained; then sodium hydroxide and stearic acid were added to the reactor, the temperature was raised to 70°C, and the reaction was stirred for 1h to obtain modified calcium carbonate; in the above reaction, the amount ratio of calcium carbonate, sodium hydroxide and stearic acid was 10g:0.06g:0.15g;
[0036] a2: Place the modified calcium carbonate and anhydrous ethanol in an ultrasonic disperser, and after ultrasonic dispersion for 30 minutes, transfer them to a reactor, add a hyperbranched modifier, control the stirring reaction rate to 200r / min, heat to 55°C, stir and react for 5 hours, filter and wash the filter cake twice, then transfer it to an oven, control the oven temperature to 100°C, and vacuum dry it for 24 hours to obtain modified calcium carbonate; in the above reaction, the amount ratio of modified calcium carbonate, anhydrous ethanol and hyperbranched modifier is 5g:50g:100mL;
[0037] The hyperbranched modifier is prepared by the following method:
[0038] b1: Dipentaerythritol, γ-glycidyloxypropyltrimethoxysilane, triethylamine and DMF were mixed and added into a reactor, the reaction rate was controlled to be 150r / min, the temperature was raised to 60°C, benzene was added after stirring for 2h, and the intermediate 1 was obtained by rotary evaporation under reduced pressure; in the above reaction, the dosage ratio of dipentaerythritol, γ-glycidyloxypropyltrimethoxysilane, triethylamine and DMF was 0.05mol:0.3mol:1.5mL:100mL; the dosage ratio of DMF and benzene was 1mL:3mL;
[0039] b2: Diethanolamine and anhydrous methanol were mixed and added to a reactor, the stirring reaction rate was controlled to be 300 r / min, and stirred in a nitrogen atmosphere until completely dissolved, and then methyl acrylate and potassium carbonate were added, the temperature was raised to 35°C, and the reaction was stirred for 4 hours, and then the intermediate 2 was obtained by rotary evaporation under reduced pressure; in the above reaction, the dosage ratio of diethanolamine, methyl acrylate, potassium carbonate and anhydrous ethanol was 0.5 mol: 0.8 mol: 1.5 g: 200 mL;
[0040] b3: Take intermediate 1, p-toluenesulfonic acid and NMP and mix them into a reactor, control the stirring reaction rate to 200r / min, heat to 90°C and stir continuously until intermediate 1 is completely dissolved, then add intermediate 2, then heat to 130°C, stir and react for 2h, add chloroform, extract and dry to obtain a hyperbranched modifier; in the above reaction, the amount ratio of intermediate 1, intermediate 2, p-toluenesulfonic acid and NMP is 0.01mol:0.06mol:0.3g:50mL; the amount ratio of NMP and chloroform is 1mL:2mL;
[0041] 2) Preparation of high-toughness phenolic adhesive
[0042] s1: 100 parts of phenolic resin (liquid phenolic resin of Henan Jieyang New Materials Co., Ltd., model 2130, is used in both the present embodiment and the comparative example), 15 parts of modified calcium carbonate, 5 parts of curing agent (hexamethylenetetramine is used in both the present embodiment and the comparative example), 3 parts of defoaming agent (dimethyl silicone oil is used in both the present embodiment and the comparative example), 5 parts of diluent (glycerol is used in both the present embodiment and the comparative example) and 2 parts of antioxidant (anti-aging agent TCY2-3 is used in both the present embodiment and the comparative example) are mixed and added into a reactor, the stirring reaction rate is controlled to be 1000r / min, the temperature is raised to 70°C, the reaction is stirred for 1h, and then cooled to room temperature to obtain a high-toughness phenolic adhesive.
[0043] Example 2
[0044] The specific implementation process of preparing a high-toughness phenolic adhesive in this embodiment is as follows:
[0045] 1) Preparation of modified calcium carbonate:
[0046] a1: 10g of calcium carbonate and deionized water were mixed and added to a reactor, the stirring rate was controlled to be 1600r / min, and after stirring for 20min, a calcium carbonate suspension with a solid content of 20% was obtained; then sodium hydroxide and stearic acid were added to the reactor, the temperature was raised to 71°C, and the reaction was stirred for 1h to obtain modified calcium carbonate; in the above reaction, the amount ratio of calcium carbonate, sodium hydroxide and stearic acid was 10g:0.06g:0.16g;
[0047] a2: Place the modified calcium carbonate and anhydrous ethanol in an ultrasonic disperser, and after ultrasonic dispersion for 30 minutes, transfer them to a reactor, add a hyperbranched modifier, control the stirring reaction rate to 220r / min, heat to 57°C, stir and react for 5 hours, filter and wash the filter cake three times, then transfer it to an oven, control the oven temperature to 100°C, and vacuum dry it for 24 hours to obtain modified calcium carbonate; in the above reaction, the amount ratio of modified calcium carbonate, anhydrous ethanol and hyperbranched modifier is 6g:50g:100mL;
[0048] The hyperbranched modifier is prepared by the following method:
[0049] b1: Dipentaerythritol, γ-glycidyloxypropyltrimethoxysilane, triethylamine and DMF were mixed and added into a reactor, the reaction rate was controlled to be 160r / min, the temperature was raised to 62°C, benzene was added after stirring for 2h, and the intermediate 1 was obtained by rotary evaporation under reduced pressure; in the above reaction, the dosage ratio of dipentaerythritol, γ-glycidyloxypropyltrimethoxysilane, triethylamine and DMF was 0.05mol:0.3mol:1.6mL:100mL; the dosage ratio of DMF and benzene was 1mL:3mL;
[0050] b2: Diethanolamine and anhydrous methanol were mixed and added to a reactor, the stirring reaction rate was controlled to be 320r / min, and the mixture was stirred in a nitrogen atmosphere until it was completely dissolved. Then, methyl acrylate and potassium carbonate were added, the temperature was raised to 36°C, and the mixture was stirred for 4 hours and then vacuum evaporated to obtain intermediate 2; in the above reaction, the dosage ratio of diethanolamine, methyl acrylate, potassium carbonate and anhydrous ethanol was 0.5mol:0.8mol:1.6g:200mL;
[0051] b3: Take intermediate 1, p-toluenesulfonic acid and NMP and mix them into a reactor, control the stirring reaction rate to 220r / min, heat to 92°C and stir continuously until intermediate 1 is completely dissolved, then add intermediate 2, then heat to 130°C, stir and react for 2h, add chloroform, extract and dry to obtain a hyperbranched modifier; in the above reaction, the amount ratio of intermediate 1, intermediate 2, p-toluenesulfonic acid and NMP is 0.01mol:0.06mol:0.4g:50mL; the amount ratio of NMP and chloroform is 1mL:2mL;
[0052] 2) Preparation of high-toughness phenolic adhesive
[0053] s1: 100 parts of phenolic resin, 17 parts of modified calcium carbonate, 6 parts of curing agent, 4 parts of defoaming agent, 6 parts of diluent and 3 parts of antioxidant were mixed and added into a reactor, the stirring reaction rate was controlled to be 1000r / min, the temperature was raised to 72°C, stirred for reaction for 1h and then cooled to room temperature to obtain a high-toughness phenolic adhesive.
[0054] Example 3
[0055] The specific implementation process of preparing a high-toughness phenolic adhesive in this embodiment is as follows:
[0056] 1) Preparation of modified calcium carbonate:
[0057] a1: 10g of calcium carbonate and deionized water were mixed and added to a reactor, the stirring rate was controlled to be 1700r / min, and after stirring for 20min, a calcium carbonate suspension with a solid content of 20% was obtained; then sodium hydroxide and stearic acid were added to the reactor, the temperature was raised to 72°C, and the reaction was stirred for 1h to obtain modified calcium carbonate; in the above reaction, the amount ratio of calcium carbonate, sodium hydroxide and stearic acid was 10g:0.06g:0.17g;
[0058] a2: Place the modified calcium carbonate and anhydrous ethanol in an ultrasonic disperser, and after ultrasonic dispersion for 30 minutes, transfer them to a reactor, add a hyperbranched modifier, control the stirring reaction rate to 240r / min, heat to 59°C, stir and react for 5 hours, filter and wash the filter cake 3 times, then transfer it to an oven, control the oven temperature to 100°C, and vacuum dry it for 24 hours to obtain modified calcium carbonate; in the above reaction, the amount ratio of modified calcium carbonate, anhydrous ethanol and hyperbranched modifier is 7g:50g:100mL;
[0059] The hyperbranched modifier is prepared by the following method:
[0060] b1: Dipentaerythritol, γ-glycidyloxypropyltrimethoxysilane, triethylamine and DMF were mixed and added into a reactor, the reaction rate was controlled to be 170r / min, the temperature was raised to 64°C, benzene was added after stirring for 2h, and the intermediate 1 was obtained by rotary evaporation under reduced pressure; in the above reaction, the dosage ratio of dipentaerythritol, γ-glycidyloxypropyltrimethoxysilane, triethylamine and DMF was 0.05mol:0.3mol:1.7mL:100mL; the dosage ratio of DMF and benzene was 1mL:3mL;
[0061] b2: Diethanolamine and anhydrous methanol were mixed and added to a reactor, the stirring reaction rate was controlled to be 340 r / min, and the mixture was stirred in a nitrogen atmosphere until it was completely dissolved. Then, methyl acrylate and potassium carbonate were added, the temperature was raised to 37°C, and the mixture was stirred for 5 hours and then vacuum evaporated to obtain intermediate 2; in the above reaction, the dosage ratio of diethanolamine, methyl acrylate, potassium carbonate and anhydrous ethanol was 0.5 mol: 0.8 mol: 1.7 g: 200 mL;
[0062] b3: Take intermediate 1, p-toluenesulfonic acid and NMP and mix them into a reactor, control the stirring reaction rate to 240r / min, heat to 94°C and stir continuously until intermediate 1 is completely dissolved, then add intermediate 2, then heat to 130°C, stir and react for 2h, add chloroform, extract and dry to obtain a hyperbranched modifier; in the above reaction, the amount ratio of intermediate 1, intermediate 2, p-toluenesulfonic acid and NMP is 0.01mol:0.06mol:0.5g:50mL; the amount ratio of NMP and chloroform is 1mL:2mL;
[0063] 2) Preparation of high-toughness phenolic adhesive
[0064] s1: 100 parts of phenolic resin, 19 parts of modified calcium carbonate, 7 parts of curing agent, 5 parts of defoaming agent, 7 parts of diluent and 2 parts of antioxidant were mixed and added into a reactor, the stirring reaction rate was controlled to be 1200r / min, the temperature was raised to 74°C, stirred for reaction for 1h and then cooled to room temperature to obtain a high-toughness phenolic adhesive.
[0065] Example 4
[0066] The specific implementation process of preparing a high-toughness phenolic adhesive in this embodiment is as follows:
[0067] 1) Preparation of modified calcium carbonate:
[0068] a1: 10g of calcium carbonate and deionized water were mixed and added to a reactor, the stirring rate was controlled to be 1800r / min, and after stirring for 20min, a calcium carbonate suspension with a solid content of 20% was obtained; then sodium hydroxide and stearic acid were added to the reactor, the temperature was raised to 73°C, and the reaction was stirred for 1h to obtain modified calcium carbonate; in the above reaction, the amount ratio of calcium carbonate, sodium hydroxide and stearic acid was 10g:0.06g:0.18g;
[0069] a2: Place the modified calcium carbonate and anhydrous ethanol in an ultrasonic disperser, and after ultrasonic dispersion for 30 minutes, transfer them to a reactor, add a hyperbranched modifier, control the stirring reaction rate to 260r / min, heat to 61°C, stir and react for 5 hours, filter and wash the filter cake 3 times, then transfer it to an oven, control the oven temperature to 100°C, and vacuum dry it for 24 hours to obtain modified calcium carbonate; in the above reaction, the amount ratio of modified calcium carbonate, anhydrous ethanol and hyperbranched modifier is 8g:50g:100mL;
[0070] The hyperbranched modifier is prepared by the following method:
[0071] b1: Dipentaerythritol, γ-glycidyloxypropyltrimethoxysilane, triethylamine and DMF were mixed and added into a reactor, the reaction rate was controlled to be 180r / min, the temperature was raised to 66°C, benzene was added after stirring for 2h, and the intermediate 1 was obtained by rotary evaporation under reduced pressure; in the above reaction, the dosage ratio of dipentaerythritol, γ-glycidyloxypropyltrimethoxysilane, triethylamine and DMF was 0.05mol:0.3mol:1.8mL:100mL; the dosage ratio of DMF and benzene was 1mL:3mL;
[0072] b2: Diethanolamine and anhydrous methanol were mixed and added into a reactor, the stirring reaction rate was controlled to be 360r / min, and the mixture was stirred in a nitrogen atmosphere until it was completely dissolved. Then, methyl acrylate and potassium carbonate were added, the temperature was raised to 38°C, and the mixture was stirred for reaction for 5 hours, and then vacuum rotary evaporation was performed to obtain intermediate 2; in the above reaction, the dosage ratio of diethanolamine, methyl acrylate, potassium carbonate and anhydrous ethanol was 0.5mol:0.8mol:1.8g:200mL;
[0073] b3: Take intermediate 1, p-toluenesulfonic acid and NMP and mix them into a reactor, control the stirring reaction rate to 260r / min, heat to 96°C and stir continuously until intermediate 1 is completely dissolved, then add intermediate 2, then heat to 130°C, stir and react for 2h, add chloroform, extract and dry to obtain a hyperbranched modifier; in the above reaction, the amount ratio of intermediate 1, intermediate 2, p-toluenesulfonic acid and NMP is 0.01mol:0.06mol:0.5g:50mL; the amount ratio of NMP and chloroform is 1mL:2mL;
[0074] 2) Preparation of high-toughness phenolic adhesive
[0075] s1: 100 parts of phenolic resin, 21 parts of modified calcium carbonate, 8 parts of curing agent, 5 parts of defoaming agent, 5 parts of diluent and 2 parts of antioxidant were mixed and added into a reactor, the stirring reaction rate was controlled to be 1300r / min, the temperature was raised to 76°C, stirred for reaction for 1h and then cooled to room temperature to obtain a high-toughness phenolic adhesive.
[0076] Example 5
[0077] The specific implementation process of preparing a high-toughness phenolic adhesive in this embodiment is as follows:
[0078] 1) Preparation of modified calcium carbonate:
[0079] a1: 10g of calcium carbonate and deionized water were mixed and added to a reactor, the stirring rate was controlled to be 1900r / min, and after stirring for 20min, a calcium carbonate suspension with a solid content of 20% was obtained; then sodium hydroxide and stearic acid were added to the reactor, the temperature was raised to 74°C, and the reaction was stirred for 1h to obtain modified calcium carbonate; in the above reaction, the amount ratio of calcium carbonate, sodium hydroxide and stearic acid was 10g:0.06g:0.19g;
[0080] a2: Place the modified calcium carbonate and anhydrous ethanol in an ultrasonic disperser, and after ultrasonic dispersion for 30 minutes, transfer them to a reactor, add a hyperbranched modifier, control the stirring reaction rate to 280r / min, heat to 63°C, stir and react for 5 hours, filter and wash the filter cake 3 times, then transfer it to an oven, control the oven temperature to 100°C, and vacuum dry it for 24 hours to obtain modified calcium carbonate; in the above reaction, the amount ratio of modified calcium carbonate, anhydrous ethanol and hyperbranched modifier is 9g:50g:100mL;
[0081] The hyperbranched modifier is prepared by the following method:
[0082] b1: Dipentaerythritol, γ-glycidyloxypropyltrimethoxysilane, triethylamine and DMF were mixed and added into a reactor, the reaction rate was controlled to be 190r / min, the temperature was raised to 68°C, benzene was added after stirring for 3h, and the intermediate 1 was obtained by rotary evaporation under reduced pressure; in the above reaction, the dosage ratio of dipentaerythritol, γ-glycidyloxypropyltrimethoxysilane, triethylamine and DMF was 0.05mol:0.3mol:1.9mL:100mL; the dosage ratio of DMF and benzene was 1mL:3mL;
[0083] b2: Diethanolamine and anhydrous methanol were mixed and added to a reactor, the stirring reaction rate was controlled to be 380 r / min, and the mixture was stirred in a nitrogen atmosphere until it was completely dissolved. Then, methyl acrylate and potassium carbonate were added, the temperature was raised to 39°C, and the mixture was stirred for 5 hours and then vacuum evaporated to obtain intermediate 2; in the above reaction, the dosage ratio of diethanolamine, methyl acrylate, potassium carbonate and anhydrous ethanol was 0.5 mol: 0.8 mol: 1.8 g: 200 mL;
[0084] b3: Take intermediate 1, p-toluenesulfonic acid and NMP and mix them into a reactor, control the stirring reaction rate to 280r / min, heat to 98°C and stir continuously until intermediate 1 is completely dissolved, then add intermediate 2, then heat to 130°C, stir and react for 2h, add chloroform, extract and dry to obtain a hyperbranched modifier; in the above reaction, the amount ratio of intermediate 1, intermediate 2, p-toluenesulfonic acid and NMP is 0.01mol:0.06mol:0.5g:50mL; the amount ratio of NMP and chloroform is 1mL:2mL;
[0085] 2) Preparation of high-toughness phenolic adhesive
[0086] s1: 100 parts of phenolic resin, 23 parts of modified calcium carbonate, 8 parts of curing agent, 5 parts of defoaming agent, 8 parts of diluent and 3 parts of antioxidant were mixed and added into a reactor, the stirring reaction rate was controlled to be 1400r / min, the temperature was raised to 78°C, stirred for reaction for 1h and then cooled to room temperature to obtain a high-toughness phenolic adhesive.
[0087] Example 6
[0088] The specific implementation process of preparing a high-toughness phenolic adhesive in this embodiment is as follows:
[0089] 1) Preparation of modified calcium carbonate:
[0090] a1: 10g of calcium carbonate and deionized water were mixed and added to a reactor, the stirring rate was controlled to be 2000r / min, and after stirring for 20min, a calcium carbonate suspension with a solid content of 20% was obtained; then sodium hydroxide and stearic acid were added to the reactor, the temperature was raised to 76°C, and the reaction was stirred for 1h to obtain modified calcium carbonate; in the above reaction, the amount ratio of calcium carbonate, sodium hydroxide and stearic acid was 10g:0.06g:0.2g;
[0091] a2: Place the modified calcium carbonate and anhydrous ethanol in an ultrasonic disperser, and after ultrasonic dispersion for 30 minutes, transfer them to a reactor, add a hyperbranched modifier, control the stirring reaction rate to 300r / min, heat to 65°C, stir and react for 5 hours, filter and wash the filter cake 3 times, then transfer it to an oven, control the oven temperature to 100°C, and vacuum dry it for 24 hours to obtain modified calcium carbonate; in the above reaction, the amount ratio of modified calcium carbonate, anhydrous ethanol and hyperbranched modifier is 10g:50g:100mL;
[0092] The hyperbranched modifier is prepared by the following method:
[0093] b1: Dipentaerythritol, γ-glycidyloxypropyltrimethoxysilane, triethylamine and DMF were mixed and added into a reactor, the reaction rate was controlled to be 200 r / min, the temperature was raised to 70°C, and benzene was added after stirring for 3 hours, and the intermediate 1 was obtained by rotary evaporation under reduced pressure; in the above reaction, the dosage ratio of dipentaerythritol, γ-glycidyloxypropyltrimethoxysilane, triethylamine and DMF was 0.05 mol: 0.3 mol: 2 mL: 100 mL; the dosage ratio of DMF and benzene was 1 mL: 3 mL;
[0094] b2: Diethanolamine and anhydrous methanol were mixed and added to a reactor, the stirring reaction rate was controlled to be 400 r / min, and the mixture was stirred in a nitrogen atmosphere until it was completely dissolved. Then, methyl acrylate and potassium carbonate were added, the temperature was raised to 40°C, and the mixture was stirred for 5 hours and then vacuum evaporated to obtain intermediate 2; in the above reaction, the dosage ratio of diethanolamine, methyl acrylate, potassium carbonate and anhydrous ethanol was 0.5 mol: 0.8 mol: 1.8 g: 200 mL;
[0095] b3: Take intermediate 1, p-toluenesulfonic acid and NMP and mix them into a reactor, control the stirring reaction rate to 300r / min, heat to 100℃ and stir continuously until intermediate 1 is completely dissolved, then add intermediate 2, then heat to 130℃, stir and react for 2h, add chloroform, extract and dry to obtain a hyperbranched modifier; in the above reaction, the amount ratio of intermediate 1, intermediate 2, p-toluenesulfonic acid and NMP is 0.01mol:0.06mol:0.5g:50mL; the amount ratio of NMP and chloroform is 1mL:2mL;
[0096] 2) Preparation of high-toughness phenolic adhesive
[0097] s1: 100 parts of phenolic resin, 25 parts of modified calcium carbonate, 8 parts of curing agent, 5 parts of defoaming agent, 8 parts of diluent and 3 parts of antioxidant were mixed and added into a reactor, the stirring reaction rate was controlled to be 1500r / min, the temperature was raised to 80°C, stirred for reaction for 1h and then cooled to room temperature to obtain a high-toughness phenolic adhesive.
[0098] Comparative Example 1
[0099] The specific implementation process of preparing the high-toughness phenolic resin adhesive in this comparative example is as follows:
[0100] 1) Preparation of modified calcium carbonate:
[0101] a1: 10g of calcium carbonate and deionized water were mixed and added to a reactor, the stirring rate was controlled to be 2000r / min, and after stirring for 20min, a calcium carbonate suspension with a solid content of 20% was obtained; then sodium hydroxide and stearic acid were added to the reactor, the temperature was raised to 76°C, and the reaction was stirred for 1h to obtain modified calcium carbonate; in the above reaction, the amount ratio of calcium carbonate, sodium hydroxide and stearic acid was 10g:0.06g:0.2g;
[0102] a2: Place the modified calcium carbonate and anhydrous ethanol in an ultrasonic disperser, ultrasonically disperse for 30 minutes, transfer to a reactor, add KH-550, control the stirring reaction rate to 300r / min, heat to 65°C, stir and react for 5 hours, filter and wash the filter cake three times, then transfer to an oven, control the oven temperature to 100°C, and vacuum dry for 24 hours to obtain the modified calcium carbonate; in the above reaction, the amount ratio of modified calcium carbonate, anhydrous ethanol and KH-550 is 15g:50g:0.75g;
[0103] 2) Preparation of high-toughness phenolic adhesive
[0104] s1: 100 parts of phenolic resin, 15 parts of terminal hydroxyl hyperbranched polyester (this comparative example uses terminal hydroxyl hyperbranched polyester from Wuhan Hyperbranched Resin Technology Co., Ltd.), 5 parts of modified calcium carbonate, 8 parts of curing agent, 5 parts of defoaming agent, 8 parts of diluent and 3 parts of antioxidant are mixed and added into a reactor, the stirring reaction rate is controlled to be 1400r / min, the temperature is raised to 80°C, stirred for reaction for 1h, and then cooled to room temperature to obtain a phenolic adhesive.
[0105] Comparative Example 2
[0106] The specific implementation process of preparing the high-toughness phenolic resin adhesive in this comparative example is as follows:
[0107] s1: 100 parts of phenolic resin, 10 parts of the terminal hydroxyl hyperbranched polyester in Comparative Example 1, 10 parts of the modified calcium carbonate in Comparative Example 1, 8 parts of a curing agent, 5 parts of a defoaming agent, 8 parts of a diluent and 3 parts of an antioxidant are mixed and added into a reactor, the stirring reaction rate is controlled to be 1400 r / min, the temperature is raised to 80°C, the reaction is stirred for 1 hour, and then cooled to room temperature to obtain a phenolic adhesive.
[0108] Comparative Example 3
[0109] This comparative example uses a phenolic resin adhesive in the CN102994027A patent.
[0110] Bending strength test:
[0111] The high-toughness phenolic adhesive prepared in Examples 1-6 and the phenolic adhesive in Comparative Examples 1-3 were placed in a mold to prepare a test sample according to GB / T9341-2000, kept at 120°C for 120 minutes, cooled at room temperature, and then tested using a universal mechanical testing machine. The specimen loading speed was 3 mm / min, and the test time was controlled within 20-200 seconds.
[0112] The high-toughness phenolic adhesives prepared in Examples 1-6 and the phenolic adhesives in Comparative Examples 1-3 were subjected to tensile strength tests, elongation tests, shear strength tests, and T-peel strength tests according to GB / T2567-2008, GB / T2568-1995, GB / T7124-2008, and ASTMD1876-08, respectively. The specific test data are shown in Table 1:
[0113] Table 1
[0114]
[0115]
[0116] It can be seen from the data in Table 1 that the high-toughness phenolic adhesive prepared in Examples 1-6 has a bending strength of 78.6-79.4 MPa, a tensile strength of 49.2-50.3 MPa, an elongation of 25.41-25.54%, a shear strength of 32.4-33.8 MPa, and a T-peel strength of 587-598 N / m. All the data are better than the phenolic adhesive prepared in Comparative Examples 1-3, indicating that the high-toughness phenolic adhesive prepared in Examples 1-6 has excellent toughness and mechanical strength.
[0117] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0118] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A high-toughness phenolic adhesive, characterized in that: The composition comprises 100 parts of phenolic resin, 15-20 parts of modified calcium carbonate, 5-8 parts of curing agent, 5-8 parts of diluent, 3-5 parts of defoaming agent and 2-3 parts of antioxidant according to weight parts; Modified calcium carbonate is prepared by the following method: Step A1: Calcium carbonate and deionized water are mixed and added, and stirred for 20 minutes to obtain a calcium carbonate suspension; then sodium hydroxide and stearic acid are added to a reaction kettle, the temperature is raised to 70-75° C., and the reaction is stirred for 1 hour to obtain modified calcium carbonate; Step A2: After the modified calcium carbonate and anhydrous ethanol are mixed and ultrasonically dispersed for 30 minutes, they are transferred to a reactor, and a hyperbranched modifier is added. The temperature is raised to 55-65° C., and the reaction is stirred for 5-6 hours. The filter cake is filtered and washed with water for 2-3 times, and then transferred to an oven and vacuum dried for 24 hours to obtain the modified calcium carbonate; The hyperbranched modifier is prepared by the following method: Step B1: dipentaerythritol, γ-glycidyloxypropyltrimethoxysilane, triethylamine and DMF were mixed and added, the temperature was raised to 60-70°C, stirred for reaction for 2-3h, benzene was added, and vacuum rotary evaporation was performed to obtain intermediate 1; Step B2: diethanolamine and anhydrous methanol were mixed and added, followed by methyl acrylate and potassium carbonate, and the temperature was raised to 35-40°C. The mixture was stirred for 4-5 hours and then vacuum evaporated to obtain intermediate 2; Step B3: Mix the intermediate 1, p-toluenesulfonic acid and NMP, heat to 90-100°C and stir continuously until the intermediate 1 is completely dissolved, then add the intermediate 2, heat to 130°C, stir and react for 2h, add chloroform, extract and dry to obtain a hyperbranched modifier; In step B1, the usage ratio of dipentaerythritol, γ-glycidyloxypropyltrimethoxysilane, triethylamine and DMF is 0.05 mol: 0.3 mol: 1.5-2 mL: 100 mL; the usage ratio of DMF and benzene is 1 mL: 3 mL; In step B2, the usage ratio of diethanolamine, methyl acrylate, potassium carbonate and anhydrous ethanol is 0.5 mol: 0.8mol: 1.5-1.8g: 200mL; In step B3, the usage ratio of intermediate 1, intermediate 2, p-toluenesulfonic acid and NMP is 0.01 mol: 0.06 mol: 0.3-0.5 g: 50 mL; the usage ratio of NMP and chloroform is 1 mL: 2 mL; A method for preparing a high-toughness phenolic adhesive comprises the following steps: Phenolic resin, modified calcium carbonate, curing agent, defoaming agent, diluent and antioxidant are mixed and added, the temperature is raised to 70-80° C., stirred for reaction for 1-2 hours, and then cooled to room temperature to obtain a high-toughness phenolic adhesive; The curing agent is hexamethylenetetramine; The defoaming agent is dimethyl silicone oil.
2. A high-toughness phenolic adhesive according to claim 1, characterized in that: In step A1, the solid content of the calcium carbonate suspension is 20%; the usage ratio of calcium carbonate, sodium hydroxide and stearic acid is 10g:0.06g:0.15-0.2g.
3. A high-toughness phenolic adhesive according to claim 2, characterized in that: In step A2, the usage ratio of modified calcium carbonate, anhydrous ethanol and hyperbranched modifier is 5-10 g:50 g:100 mL.
